An introduction to ordinary differential equations - Costa, Fernando Pestana da (2017)
This text was prepared as support to a training workshop for teachers of the University of Savannakhet, Laos. Its objective is to provide a very brief introduction to modelling using differential equations, and to present the subject so as to stress basic principles and methods, as well as to point to required background in Mathematical Analysis that further serious study will require.